Smartphone dependence: A socio-physiological nightmare - Rashid, Arsalaan F; Aggarwal, Akashdeep; Noor, Farida; Jehan, Masarat (Journal of Indian Academy of Forensic Medicine, 2021)
Smartphone has become a common platform for communication, education, entertainment, infotainment. Not only has such diverse  usage made it an indispensable item of daily usage but its infiltration into our personal lives in form of social media platforms like  Facebook, WhatsApp etc have put a lot of strain on our social interactions. A combination of multipurpose usage and socialization has  made smartphone and its dependence producing habit a subject of intense studies in recent past. Present study is exceptional and  productive because it utilizes the environment of sudden depravation of smartphone usage and applies the withdrawal produced by it  in understanding the basic human socio-physiological response. This study is also unique by the fact that predominant population  used in the study, had a professional medical background and were more accurate in providing data especially related to physiological  aspect of study.
Keywords: Smartphone; Social media; Multipurpose usage; Dependence; Socialization; Physiological